The ocean tide beneath the Ross Ice Shelf - Williams, Richard T. (Virginia Tech, 1976)
Measurements of the ocean tide beneath the Ross Ice Shelf by a gravimetric method at five locations (79.3°S, 189.7°W; 79.8°S, 169.1°W; 80.2°S, 161.6°W; 82.5°S, 166.0°W; 78.2°S, 162.3°W), and conventional sea level measurements at one location (77.9°S, 193.4°W), show that the diurnal constituents of the tide account for approximately 75% of the tidal fluctuation of the thickness of the water layer beneath the shelf, at times of spring tide. In the gravimetric method, fluctuations in the gravity on the surface of the ice shelf are attributed to changes in elevation and water mass beneath the gravimeter, due to changes in the thickness of the water layer. The amplitudes of the diurnal constituents PK and 0 increase from approximately 30 cm and 20 cm, respectively, near Ross Island at the northwestern extremity of the ice shelf, to twice those values at the southern extremity. The amplitudes of the semidiurnal constituents M, N, and S are generally less than 10 cm, with the largest amplitudes occurring beneath the southern portion of the shelf. Cotidal lines for the diurnal constituents trend north to northwest. The phase, relative to Greenwich, is between 150° and 210° for PK, and 140° and 200° for 0. The phases of the diurnal constituents of the tide in the southern Ross Sea are consistent with the phases of corresponding constituents in the southern Pacific Ocean. Tidal currents, inferred from the shape of the sea-surface by means of the Laplace Tidal Equations, were found to be. generally less than 20 cm/sec at times of spring tide. Maximum currents occur in a northwest trending zone in the southern part of the area where the water layer is most thin. Master of Science